Prognostic value of kallikrein-related peptidase 7 (KLK7) mRNA expression in advanced high-grade serous ovarian cancer - Gong, Weiwei; Liu, Yueyang; Diamandis, Eleftherios P.; Kiechle, Marion; Bronger, Holger; Dorn, Julia; Dreyer, Tobias; Magdolen, Viktor (Journal of ovarian research, 2020)
Background High-grade serous ovarian cancer (HGSOC) is the most common and lethal subtype of ovarian cancer. A growing body of evidence suggests tumor-supporting roles of several members of the kallikrein-related peptidase (KLK) family, including KLK5 and KLK7, in this cancer subtype. In normal physiology, KLK5 and KLK7 are the major proteases involved in skin desquamation. Moreover, in several cancer types KLK5 and KLK7 co-expression has been observed. Recently, we have shown that elevated KLK5 mRNA levels are associated with an unfavorable prognosis in HGSOC. Therefore, the aim of this study was to investigate the clinical significance of KLK7 mRNA expression and to explore its relation to KLK5 levels in HGSOC. Methods mRNA expression levels of KLK7 were quantified by qPCR in a well-characterized patient cohort afflicted with advanced high-grade serous ovarian cancer (FIGO III/IV, n = 139). Previously determined KLK5 mRNA as well as KLK5 and KLK7 antigen concentrations were used to evaluate the relationship between the expression patterns of both factors on the mRNA as well as protein level in tumor tissue of HGSOC patients. Results There were strong, significant positive correlations between KLK5 and KLK7 both at the mRNA and the protein level, suggesting coordinate expression of these proteases in HGSOC. In univariate analyses, elevated KLK7 levels as well as the combination of KLK5 + KLK7 (high and/or high versus low/low) were significantly associated with worse progression-free survival (PFS). High mRNA expression levels of KLK7 and the combination of KLK5 and KLK7 showed a trend towards significance for overall survival (OS). In multivariate analyses, KLK7 mRNA expression represented an unfavorable, statistically significant independent predictor for PFS and OS. Conclusions The findings imply that both increased KLK5 and KLK7 mRNA expression levels represent unfavorable prognostic biomarkers in advanced high-grade serous ovarian cancer, whereby multivariate analyses indicate that KLK7 mRNA exhibits a stronger predictive value as compared to KLK5 mRNA and the combination of KLK5 and KLK7.